2022
DOI: 10.3389/fimmu.2022.863657
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Mannan Oligosaccharides Enhance the Non-Specific Immunity, Intestinal Health, and Resistance Capacity of Juvenile Blunt Snout Bream (Megalobrama amblycephala) Against Aeromonas hydrophila

Abstract: Mannan oligosaccharides (MOS) have been studied and applied as a feed additive, whereas their regulation on the growth performance and immunity of aquatic animals lacks consensus. Furthermore, their immunoprotective effects on the freshwater fish Megalobrama amblycephala have not been sufficiently studied. Thus, we investigated the effects of dietary MOS of 0, 200, and 400 mg/kg on the growth performance, non-specific immunity, intestinal health, and resistance to Aeromonas hydrophila infection in juvenile M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In the current study, by examining the mRNA levels of multiple studied inflammatory cytokines, the data from all three intestinal segments showed that almost all of the studied pro-inflammatory cytokines were down-regulated (except INFγ2 in the MI) with optimal MOS supplementation (400-800 mg/kg), whereas studied pro-inflammatory cytokines anti-inflammatory cytokines were up-regulated (except IL-4/13B in all three segments) with optimal MOS supplementation (400-600 mg/kg). Similarly, MOS reduced TNFα and IL-6 expression in the intestine after A. hydrophila challenged in Blunt Snout Bream ( Megalobrama amblycephala ) ( 47 ). Thus, we believe that MOS has a positive prebiotic effect on the fish intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, by examining the mRNA levels of multiple studied inflammatory cytokines, the data from all three intestinal segments showed that almost all of the studied pro-inflammatory cytokines were down-regulated (except INFγ2 in the MI) with optimal MOS supplementation (400-800 mg/kg), whereas studied pro-inflammatory cytokines anti-inflammatory cytokines were up-regulated (except IL-4/13B in all three segments) with optimal MOS supplementation (400-600 mg/kg). Similarly, MOS reduced TNFα and IL-6 expression in the intestine after A. hydrophila challenged in Blunt Snout Bream ( Megalobrama amblycephala ) ( 47 ). Thus, we believe that MOS has a positive prebiotic effect on the fish intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with a previous study (39), we stained the fish midgut with hematoxylin and eosin to observe effects of exogenous cysteine on the intestinal physical barrier. Briefly, the midguts were stored in a 4% paraformaldehyde solution for 24 h. We used ethanol to gradually eliminate the moisture.…”
Section: Midgut Histological Examinationmentioning
confidence: 94%
“…According to previous studies ( 39 , 40 ), total DNA of intestinal bacteria was obtained using a DNA extraction kit (TIANGEN BIOTECH Co., Ltd., Beijing, China), DNA integrity was assessed using 1% agarose gel electrophoresis, and concentration was measured using a Nanodrop 2000 device (Thermo Fisher Scientific, Waltham, MA, USA). The DNA samples were diluted to 1 ng·μL -1 using sterile water, and PCR amplification of the bacterial 16S rDNA V3–V4 variable region was performed using specific primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described by Ding et al (36), we subjected golden pompano midguts to hematoxylin and eosin (H&E) staining to observe histological structures. First, the midgut was fixed in 4% paraformaldehyde solution for 24 h and dehydrated via ethanol grading.…”
Section: Midgut Histological Observationmentioning
confidence: 99%